Money Creation in Decentralized Finance: A Dynamic Model of Stablecoin and Crypto Shadow Banking - Ye Li; Simon Mayer (Center for Economic Studies and ifo Institute (CESifo), 2021)
Stablecoins rise to meet the demand for safe assets in decentralized finance. Stablecoin issuers transform risky reserve assets into tokens of stable values, deploying a variety of tactics. To address the questions on the viability of stablecoins, regulations, and the initiatives led by large platforms, we develop a dynamic model of optimal stablecoin management and characterize an instability trap. The system is bimodal: stability can last for a long time, but once stablecoins break the buck following negative shocks, volatility persists. Debasement triggers a vicious cycle but is unavoidable as it allows efficient risk sharing between the issuer and stablecoin users.
Keywords: E41; E42; E51; E52; F31; G12; G18; G21; G31; G32; G35; L14; L86; 330; stablecoin; instability; regulation; debasement; big data; payment; collateral; shadow banking